(+)-Catechin inhibits heart mitochondrial complex I and nitric oxide synthase: functional consequences on membrane potential and hydrogen peroxide production. Issue 5 (17th April 2019) - Iglesias, Darío E.; Bombicino, Silvina S.; Boveris, Alberto; Valdez, Laura B.
Abstract : The aim was to study the in vitro effect of nM to low μM concentration of (+)-catechin on the enzymatic activities of mitochondrial complex I and mtNOS, as well as the consequences on the membrane potential and H2 O2 production rate. Abstract : In order to study the in vitro effect of flavan-3-ol (+)-catechin on the enzymatic activities of mitochondrial complex I and nitric oxide synthase (mtNOS), as well as the consequences on the membrane potential and H2 O2 production rate, isolated mitochondria from rat heart were exposed to 3 nM to 100 μM (+)-catechin. NADH–Q1 reductase (complex I) and mtNOS activities were inhibited 25% and 50%, respectively, by the addition of 10 nM (+)-catechin to the reaction medium. Moreover, in the nM range, (+)-catechin decreased state 4 mitochondrial membrane potential by about 10 mV, but failed to change the membrane potential measured in the presence of ADP. (+)-Catechin (10 nM) inhibited not only complex I activity, but also the H2 O2 production rate (35%) sustained by malate–glutamate, in accordance with the decrease observed in mitochondrial membrane potential. Considering (+)-catechin concentrations lower than 10 nM, linear and positive correlations were obtained between mitochondrial complex I activity and either NO ( r 2 = 0.973) or H2 O2 production rates ( r 2 = 0.958), suggesting a functional association among these parameters. Altogether, the results indicate that (+)-catechin, at nM concentrations, inhibits mitochondrial complex I activity, leading to membrane potential decline and consequently to reduction in H2 O2 and NO production rates. The decrease in mtNOS activity could also be a consequence of the direct action of (+)-catechin on the NOS structure, this effect being in accordance with the functional interaction between complex I and mtNOS, as previously reported.